Mitochondrial diseases in North America: An analysis of the NAMDC Registry. (April 2020) - Barca, Emanuele; Long, Yuelin; Cooley, Victoria; Schoenaker, Robert; Emmanuele, Valentina; DiMauro, Salvatore; Cohen, Bruce H.; Karaa, Amel; Vladutiu, Georgirene D.; Haas, Richard; Van Hove, Johan L.K.; Scaglia, Fernando; et al.
Abstract : Objective: To describe clinical, biochemical, and genetic features of participants with mitochondrial diseases (MtDs) enrolled in the North American Mitochondrial Disease Consortium (NAMDC) Registry. Methods: This cross-sectional, multicenter, retrospective database analysis evaluates the phenotypic and molecular characteristics of participants enrolled in the NAMDC Registry from September 2011 to December 2018. The NAMDC is a network of 17 centers with expertise in MtDs and includes both adult and pediatric specialists. Results: One thousand four hundred ten of 1, 553 participants had sufficient clinical data for analysis. For this study, we included only participants with molecular genetic diagnoses (n = 666). Age at onset ranged from infancy to adulthood. The most common diagnosis was multisystemic disorder (113 participants), and only a minority of participants were diagnosed with a classical mitochondrial syndrome. The most frequent classical syndromes were Leigh syndrome (97 individuals) and mitochondrial encephalomyopathy, lactic acidosis, and stroke-like episodes (71 individuals). Pathogenic variants in the mitochondrial DNA were more frequently observed (414 participants) than pathogenic nuclear gene variants (252 participants). Pathogenic variants in 65 nuclear genes were identified, with POLG1 and PDHA1 being the most commonly affected. Pathogenic variants in 38 genes were reported only in single participants. Conclusions: The NAMDC Registry data confirm the high variability of clinical, biochemical, and genetic features of participants with MtDs. This study serves as an important resource for future enhancement of MtD research and clinical care by providing the first comprehensive description of participant with MtD in North America.